Whole Genome DNA Methylation Analysis of Obstructive Sleep Apnea: IL1R2, NPR2 , AR , SP140 Methylation and Clinical Phenotype - Chen, Yung-Che; Chen, Ting-Wen; Su, Mao-Chang; Chen, Chung-Jen; Chen, Kuang-Den; Liou, Chia-Wei; Tang, Petrus; Wang, Ting-Ya; Chang, Jen-Chieh; Wang, Chin-Chou; Lin, Hsin-Ching; Chin, Chien-Hung; et al. (Sleep (New York, N.Y.), 2016)
We hypothesized that DNA methylation patterns may contribute to disease severity or the development of hypertension and excessive daytime sleepiness (EDS) in patients with obstructive sleep apnea (OSA). Illumina's (San Diego, CA, USA) DNA methylation 27-K assay was used to identify differentially methylated loci (DML). DNA methylation levels were validated by pyrosequencing. A discovery cohort of 15 patients with OSA and 6 healthy subjects, and a validation cohort of 72 patients with sleep disordered breathing (SDB). Microarray analysis identified 636 DMLs in patients with OSA versus healthy subjects, and 327 DMLs in patients with OSA and hypertension versus those without hypertension. In the validation cohort, no significant difference in DNA methylation levels of six selected genes was found between the primary snoring subjects and OSA patients (primary outcome). However, a secondary outcome analysis showed that interleukin-1 receptor 2 (IL1R2) promoter methylation (-114 cytosine followed by guanine dinucleotide sequence [CpG] site) was decreased and IL1R2 protein levels were increased in the patients with SDB with an oxygen desaturation index > 30. Androgen receptor (AR) promoter methylation (-531 CpG site) and AR protein levels were both increased in the patients with SDB with an oxygen desaturation index > 30. Natriuretic peptide receptor 2 (NPR2) promoter methylation (-608/-618 CpG sites) were decreased, whereas levels of both NPR2 and serum C type natriuretic peptide protein were increased in the SDB patients with EDS. Speckled protein 140 (SP140) promoter methylation (-194 CpG site) was increased, and SP140 protein levels were decreased in the patients with SDB and EDS. IL1R2 hypomethylation and AR hypermethylation may constitute an important determinant of disease severity, whereas NPR2 hypomethylation and SP140 hypermethylation may provide a biomarker for vulnerability to EDS in OSA. A commentary on this article appears in this issue on page 723.